Financiamiento de micro y pequeñas empresas del sector industrial y su efecto en el desarrollo socio económico de Trujillo - Mucha Paitán, Mariano (2009)
In this progress research work, the effect of the financing granted by the national bank to the Micro and Small Enterprises (MYPES) of the industrial sector of the city of Trujillo-Perú on the local socio-economic development has been evaluated. It was elaborated and implemented a survey to MYPES representatives on funding, training of managers, MYPES incomes, achieved socio-economic development, cost of capital, among other things. The MYPES were classified according to the amount of credit received and its investment. The data collected from the survey was complemented with data about the evolution of direct loans for the year 2007 to 2008 provided by the national bank. Likewise, it was compiled and examined data from the years 2007 and 2008 on the economy - financial information of the MYPES. We conclude that: 1) the credit support of the national bank to the MYPES is essential to enable financial leverage, 2) funding significantly impacted the growth of MYPES of the industrial sector and in turn feeds back into the socio - economic development of the province of Trujillo, 3) The MYPES have contributed to the socio-economic development of the province of Trujillo by generating more jobs and increasing the per capita level of families that interact with them, 4) due to financing from the national banking, the population of the province Trujillo segment has increased its workforce, its capacity for savings and purchasing power.